THE EFFECT OF USING PICTURE MEDIA IN TEACHING WRITING OF DESCRIPTIVE TEXT - Moh. Mahmud; Ulfatul Lasiyati (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
This experimental research was held at SMK Darussalam Blokagung. The author conducted research in two classes. The first class X KS 1 as a control class and the second class X AK 1 as an experimental class. The experimental class was taught to write descriptive text using image media, while the control class was taught to write descriptive text using the lecture method / worksheets. In analyzing the data, researchers used quantitative measurements to find the results. Where the research data collection techniques using tests. And the data analysis technique used the t-test hypothesis test. The results of the research that have been done are the value of the t count hypothesis test of 1,98 and the value of the t table of 1,67 it means, the value of t count is greater than t table. Thus, it shows the significance between picture media (X) on descriptive text writing (Y). Based on the results of the research above, it can be concluded that there is an effect of picture media on teaching writing descriptive text at X AK 1 SMK Darussalam Blokagung and it is suggested that using picture media can be used by teachers to improve students' ability in writing descriptive text. This can be applied in the teaching and learning process of English as a medium in teaching and learning activities.